A Simple Medical Record System of Non-Invasive Blood Glucose Level Measurement Results for Diabetes Care Using Graphical User Interface (GUI) MATLAB - Ahniar, Nur Hasanah; Hidayati, Rinda Nur; Lestari, Gita Rindang (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2021)
Diabetes is a chronic metabolic disorder caused by a decrease in the pancreas to produce insulin. We present a medical records system and reminders to patients of the measurement results of non-invasive blood glucose levels. Measuring blood glucose levels is vital in avoiding potential adverse health effects like diabetes. Generally, measuring blood glucose levels using the conventional method is injure the patient's finger. Currently, the non-invasive method was famous as one of the detections of blood glucose by applying the physical properties of laser absorption. In this paper, we use the photodiode as a detector, the LED as a sensor, and a signal conditioning circuit. The results showed that non-invasive glucose monitoring has the potential to measure glucose levels with sensitivity and linearity of 3.21 mg/dL and 98%, respectively. As a result of measuring the blood glucose levels of the subject was displayed on the LCD module was designed. We designed a simple application and medical record using Blynk applications and GUI MATLAB for recording the measurement results of blood glucose level. In the future, applications that have been developed can be used by doctors for monitoring the measurement of the blood glucose level and provide information to patients by mobile applications, sending an email or message the measurement results, the decision of a disease or not, and reminds the re-measurement time